Case report: Primary breast osteosarcoma: a case study and literature review - Wei, Jingxin; Luo, Xiang; Li, Xueping; Li, Junqiang; Liang, Yanling (Frontiers in Oncology, 2024)
Primary breast osteosarcoma (PBOS) is an extremely rare and poor prognostic malignancy. Here, we presented a 44-year-old female with a primary osteosarcoma of the breast (POB). Comprehensive imaging examinations conducted on the patient can be used to expand the imaging database for cases of breast osteosarcoma.